EFEKTIVITAS PELAKSANAAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN APARATUR SIPIL NEGARA DI DINAS PENDIDIKAN KABUPATEN KEPULAUAN SANGIHE - MAKAWIMBANG, RUTRISME ALICIA; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2020)
The existence of professional apparatus in various public institutions is still limited, it is necessary to getserious attention to the implementation of government duties and education services can be realizedoptimally. Based on the problem then the purpose of this research is to know how effectiveness of theimplementation of education and training in the leadership of civil state apparatus in the Sangihe IslandsDistrict Education Office.This research aims to determine the effectiveness of the development supervision function by the DistrictEducation Office of Sangihe Islands. Therefore, in order for this research to know clearly related to thepurpose of this research, the authors chose to use a descriptive research method with a qualitative approach.By applying a qualitative approach has a broader opportunity to interact with the research object, so as toenrich and deepen the study in the research the author is doing. The analytical technique used in thisresearch is a qualitative analysis technique which is a research procedure that generates descriptive data inboth written and oral words. The approach in this method of analysis is to use interactive analysisThe results showed that the implementation of the ASN leadership training in the Sangihe Islands DistrictEducation Office can be said to be ineffective because it is not suitable for the purpose that has beenestablished or what is expected. Judging from the timeliness of the implementation of training time so farthere are many ASN who are still in line waiting for the turn can be included in training Tepatan time oftraining by the district and provincial Training agency, making the performance of training body becomeineffective. Judging from the benefit dimension of training implementation of ASN ability especially ineducation environment need to be done evenly and contributed on all ASN in order to increase competencein accordance with standardization teachers will be professional in planning and managing learningprocess in school.Keywords: effectiveness, education and training, leadership, civil apparatus of the state